Scientific Mobility and Knowledge Networks in High Emigration Countries: Evidence from the Pacific - John Gibson; David McKenzie (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2013)
This paper uses a unique survey to examine the nature and extent of knowledge flows that result from the international mobility of researchers whose initial education was in small island countries. Current migrants produce substantially more research than similar-skilled return migrants and non-migrants. Return migrants have no greater research impact than individuals who never migrate but are the main source of research knowledge transfer between international and local researchers. Our results contrast with previous claims in the literature that too few migrant researchers ever return home to have much impact, and that there is no productivity gain to researchers from migration.
Keywords: J6; O3; R1; 330; Diasporas; Knowledge networks; Scientific mobility